Analysis Of The Influence Of E-Commerce Platform Types On Purchasing Behavior Through Live Shopping Features In Indonesia Using PLS-SEM - Nabila Az Zhahra; Rizqa Amelia Zunaidi; Ayu Endah Wahyuni (eProceedings of Engineering, 2025)
Abstract — This study investigates the influence of various e-commerce platforms on consumers' purchasing behavior through live shopping features in Indonesia. Employing the Theory of Planned Behavior (TPB) and integrating variables such as trust and online live shopping experience, the study uses a quantitative approach with Multigroup Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze responses from 500 users of Shopee, Tokopedia, TikTok, and Lazada. Results indicate that platform differences significantly affect the Trust–Attitude pathway, particularly on Shopee and TikTok, while Attitude, Subjective Norm, and Perceived Behavioral Control consistently influence purchase intention across all platforms. Furthermore, Intention to Live Shopping strongly predicts actual purchasing behavior. The study highlights the necessity for e-commerce businesses to tailor live shopping strategies according to platform-specific characteristics and consumer profiles. These findings contribute both theoretically and practically to understanding digital consumer behavior in the evolving landscape of social commerce. Keywords— Live Shopping, E-Commerce Platform, Purchase Intention, PLS-SEM, Consumer Behavior.